Intersectionality and Sociology: Theories and Methodologies Applied to Studies of Gender and Sexuality in Italy. Dilemmas and Perspectives - Fornari, Silvia; Nocenzi, Mariella (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The attention of the social sciences in Italy to intersectionality has only gained significant prominence in recent years when models applied to European policies were used to define policies and reform plans. In the meantime, research, especially in the social sphere, has made greater use of the literature produced over more than four decades by the North American transdisciplinary community, which in Italy was already known only to a very few, albeit unheard of, scholars. This monographic issue attempts to describe the introduction of the intersectional perspective in the Italian social and cultural context through some of the essays presented at a conference organised by the Gender Studies Section of the National Association of Sociology. The aim of that event was to reflect on the dilemmas and perspectives of intersectionality from a sociological point of view in the light of its theoretical and methodological application in gender studies in Italy, bearing in mind that the Italian scientific community has practically not experienced the long phases of maturation and institutionalisation that took place overseas. The essays in this issue pragmatically use intersectionality by applying it to different case studies - from gender violence to disability and maternity, up to families in conditions of economic deprivation - responding with the analysis of the Italian context to dilemmas and perspectives of intersectional studies on which the debate is now open among North American and international scientists.